2007
DOI: 10.1099/mic.0.2006/003814-0
|View full text |Cite
|
Sign up to set email alerts
|

The surface physicochemistry and adhesiveness of Shewanella are affected by their surface polysaccharides

Abstract: Shewanella strains have previously been studied with regard to their cell surface ultrastructure and LPS composition. They have now been further characterized with respect to their surface physicochemistry and ability to adhere to haematite. The surfaces of the Shewanella strains were found to be electronegative and hydrophilic, and these properties could be correlated with LPS composition or the presence of capsular polysaccharides. Strains expressing rough LPS with no capsule were more hydrophobic and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 61 publications
4
52
0
Order By: Relevance
“…Unlike many Gram-negative bacteria, including most Shewanella strains with ζ values ranging from −30 to −40 mV, S. oneidensis MR-1 cells possess a relatively low surface charge: a few mV at circumneutral pH and an ionic strength of 0.01. 35 Our results confirm previous findings (Table 2), with surface charge values ranging from −3.2 to −3.9 mV for S. oneidensis MR-1 in the initial stage of the experiment. Interestingly, the zeta potential becomes more negative during the course of microbial U(VI) reduction.…”
Section: Resultssupporting
confidence: 92%
“…Unlike many Gram-negative bacteria, including most Shewanella strains with ζ values ranging from −30 to −40 mV, S. oneidensis MR-1 cells possess a relatively low surface charge: a few mV at circumneutral pH and an ionic strength of 0.01. 35 Our results confirm previous findings (Table 2), with surface charge values ranging from −3.2 to −3.9 mV for S. oneidensis MR-1 in the initial stage of the experiment. Interestingly, the zeta potential becomes more negative during the course of microbial U(VI) reduction.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies demonstrated that cell surface charges and hydrophobicity play an important role in cell adhesion to biotic and abiotic surfaces (25,41,42). Hydrophobic interactions have been shown to be an important factor controlling the adhesion of Shewanella cells to amorphous Fe(III) oxide (41).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic interactions have been shown to be an important factor controlling the adhesion of Shewanella cells to amorphous Fe(III) oxide (41). Comparative analyses of the abilities of several different Shewanella strains to adhere to hematite (␣-Fe 2 O 3 ) revealed that strains with more hydrophobic and electronegative cell surfaces exhibited better adhesion (42). In addition, Shewanella cells with a more hydrophobic and electronegative surface have been shown to enhance not only cell adhesion to graphite electrodes but also cell-cell adhesion as evidenced by strong autoaggregation (25).…”
Section: Resultsmentioning
confidence: 99%
“…For the measurement of contact angles, a sessile drop technique based on the method of Korenevsky and Beveridge was performed (27). Briefly, overnight cultures of P. aeruginosa cells were harvested and washed twice with a sterile buffer (0.1 M NaCl-0.05 M HEPES [pH 7.4]) and adjusted to an OD 600 of 1.0 in a 10-ml volume of the buffer.…”
Section: Methodsmentioning
confidence: 99%